Cosmic Structure Formation with Kinetic Field Theory. Issue 11 (23rd September 2019) - Bartelmann, Matthias; Kozlikin, Elena; Lilow, Robert; Littek, Carsten; Fabis, Felix; Kostyuk, Ivan; Viermann, Celia; Heisenberg, Lavinia; Konrad, Sara; Geiss, Daniel
Abstract: Kinetic field theory (KFT) is a statistical field theory for an ensemble of classical point particles in or out of equilibrium. Its application to cosmological structure formation is reviewed. Beginning with the construction of a generating functional, it is described in detail how the theory needs to be adapted to an expanding spatial background and the homogeneous and isotropic, correlated initial conditions for cosmic structures. Based on the generating functional, three approaches are developed to nonlinear cosmic structures, which rest either on expanding an interaction operator, averaging the interaction term, or resumming perturbation terms. An analytic, parameter‐free equation for the nonlinear cosmic power spectrum is presented. It is explained how density profiles of bound structures and velocity power spectra can be derived from the theory. It is clarified how KFT relates to the BBGKY hierarchy. Kinetic field theory is then applied to fluids, reformulating KFT in terms of macroscopic quantities. The resulting resummation scheme is used to describe mixtures of gas and dark matter. Finally, it is discussed how KFT can be combined with modified theories of gravity. As an example for a noncosmological application, results are shown on the spatial correlation function of cold Rydberg atoms derived from KFT. Abstract : A statistical field theory for classical particle ensembles in or out of equilibrium and its application to cosmic structure formation is described. One main result is an analytic expression for nonlinear density power spectrum. Further applications concern the density profile of bound structures, velocity power spectra, mixtures of gas and dark matter, and structure formation in modified theories of gravity.